(untitled) (Jurnal Bahasa, 2014)
The Duano or Dossin Dolak tribe is a group of Proto-Malay indigenous peoples found in Malaysia which is separate from the Senoi and Negrito groups. The majority of this tribe dwells on the west coast of Johore. This paper focuses on the Duano or Dossin Dolak living in Kampung Pontian Besar, Kampung Bumiputera Dalam and Kampung Kuala Benut. Most of the Duanos are fishermen, merchants, labourers and factory workers. This study focuses on the counting system of that particular language. The system is studied based on the cardinal and ordinal subsystems which are present in their everyday lives. There are many similarities between the Duano and the Malay language when it comes to counting. Probably this similarity is due to their dealings with the Malays in economic activities and business transactions, such as the Duanos in Kampung Bumiputera Dalam who are well-known for their business selling second-hand furniture from Singapore. Keywords: Proto-Malay indigenous peoples, indigenous tribes, Duano, counting system, cardinals, ordinals